pH-Responsive Host-Guest Complexations Between a Water-Soluble Pillar[6]arene Dodecyl-Ammonium Chloride and Aromatic Sulfonic Acids - Duan, Qunpeng; Wang, Fei; Zhang, Hongsong; Lu, Kui (Frontiers in Chemistry, 2020)
In the present work, new host-guest binding motifs based on a water-soluble pillar[6]arene dodecyl-ammonium chloride (CP6) with two aromatic sulfonic acids in aqueous media were fabricated. In accordance with the integrated results of 1H NMR, 2D NOESY, and florescence titration experiments, it was demonstrated that the host-guest binding of CP6 with the two aromatic sulfonic acids in aqueous solution not only has high binding constants but also has pH-responsiveness.